2017
DOI: 10.3201/eid2311.170807
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Dengue Virus Infections in Children, Western Kenya, 2014–2015

Abstract: We detected a cluster of dengue virus infections in children in Kenya during July 2014–June 2015. Most cases were serotype 1, but we detected all 4 serotypes, including co-infections with 2 serotypes. Our findings implicate dengue as a cause of febrile illness in this population and highlight a need for robust arbovirus surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…We recorded higher DENV seroprevalence rates than in previous studies (Geser et al, 1970;Mease et al, 2011;Ochieng et al, 2015;Grossi-Soyster et al, 2017), whereas a concurrent study found higher DENV2 antibodies (Awando et al, 2013). DENV RNA was reported in 7.4% of children in a separate study (Vu et al, 2017). The increasing rates may be an indicator of the continuing spread of DENV from the Kenyan Coast where it has been more prevalent.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…We recorded higher DENV seroprevalence rates than in previous studies (Geser et al, 1970;Mease et al, 2011;Ochieng et al, 2015;Grossi-Soyster et al, 2017), whereas a concurrent study found higher DENV2 antibodies (Awando et al, 2013). DENV RNA was reported in 7.4% of children in a separate study (Vu et al, 2017). The increasing rates may be an indicator of the continuing spread of DENV from the Kenyan Coast where it has been more prevalent.…”
Section: Discussioncontrasting
confidence: 42%
“…The differences seen in these studies may be attributed to the different detection methods used at the time (Geser et al, 1970;Vu et al, 2017), different time periods (Geser et al,1970;Vu et al, 2017), different climatic conditions or geographic regions (Kwallah et al, 2015;Mease et al, 2011;Vu et al, 2017), or different environmental, vector, andhost dynamics (Grossi-Soyster et al, 2017;Ngugi et al, 2017;Ndenga et al, 2017;Mwongula et al, 2013;Awando et al, 2013;Kwallah et al, 2015;Ochieng et al, 2015;Vu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The IgG IFA titres ranged from 10 to 2560. 12 samples had low titres (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), 31 samples had intermediate titers and 7 samples had high titers (640-2560). For one sample, the titre could not be determined after the initial screening dilution due to a lack of sample volume.…”
Section: Diagnostic Assay Resultsmentioning
confidence: 99%
“…During 2011-2014 samples of febrile patients were studied for dengue in Nairobi, northern and coastal Kenya resulting in detection of DENV-1-3, DENV-1 was reported to be the dominating serotype [13]. DENV-1 was also reported to be the dominating serotype in febrile children of Chuilambo and Kisumu, Western Kenya in 2014-2015, with all the four DENV serotypes detected by using DENV typing RT-PCR [14]. The main vector of DENV Aedes (Stegomyia) aegypti is known to be present in western parts and the coastal region of Kenya [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that both diseases have long-term effects. Of note, dengue patients are fully recovered at 1 month postinfection, and fare worse with malaria coinfection (Vu et al, 2017).…”
Section: Antonín Holý Memorial Award: Chris Meier University Of Hambmentioning
confidence: 99%